SURAU TUA DALAM RELIEF KRIYA KAYU - RINDO PRAMONO, Drs. Irwan, M.Sn., Drs. Efrizal, M.Pd. (Serupa The Journal of Art Education, 2018)
This final work aims to visualize the old mosque building in the form of wood relief carvings, so that people know the current state of the old surau building. The data of this final work is the result of direct observation of old building buildings. Sources of data are oral sources that are directed by the informant, data is collected using interview methods, see, and recording techniques and note-taking techniques as an advanced technique for processing data. The observation findings for this final work prioritize the physical shape of the old surau building as the main object in relief carvings. The relief carvings visualize seven pieces of old surau buildings in Minangkabau.Kata kunci: surau tua. Relief. Kayu